Import demand for intermediate goods in Mexico 1993-2018 - José Romero; Rodrigo Aliphat (Atlantic Review of Economics (ARoEc), 2019)
In this paper, we study the import of intermediate goods (MIG) for México, these imports represent 80% of total imports, and they are closely related to exports and production for domestic demand. We first try to estimate a VEC model using MIG, exports, domestic demand, and real exchange rates but we find impossible to estimate directly due to problems of endogeneity between MIG, exports and domestic demand. We construct instrumental variables for exports and domestic demand. But then we face multicollinearity problems between the instrumental variables. Therefore, we estimate two separate VECs one for MIG for exports and another for MIG for domestic demand. We find minimal possibilities to increase local content for exports, but we find hope in the production for domestic demand.
Keywords: F02; F14; F15; 330; VEC; Imports; Intermediate goods; Mexico